Konstruksi Teologis dalam Oposisi Hanbali terhadap Kebijakan Pemerintahan Abbasiyah - Sholehan, Sholehan; Zuhri, Achmad Muhibbin; Fahmi, Muhammad; Syaifuddin, Syaifuddin; Dwijo, Al Qudus Nofiandri Eko Sucipto; Suwatah, Suwatah (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2023)
Opposition to the government is not a new phenomenon in the history of Islam. Imam Ahmad ibn Hanbal was a hadith scholar who once opposed the Abbasiyah government during the reign of Caliph Al-Ma'mun. This article aims to explain the theological framework of Imam Hanbali's opposition to the government of his time. Through a literature review using a content analysis approach, this article presents a historical account of the theological factors that led Imam Hanbali to oppose the government. Among the theological factors that triggered Hanbali's opposition was the doctrine of the createdness of the Quran according to the Mu'tazilah and the rulers of that time. On the other hand, Ahmad ibn Hanbal argued that the Quran was not a creation but rather the sacred word of Allah. Hanbali's opposition was not synonymous with rebellion against the rulers, but it was undertaken to safeguard the authority of religious knowledge. Imam Hanbali steadfastly endeavored to uphold the orthodox teachings of Islam derived from the Quran and Hadith. This thesis leads to the stance that opposing the government is permissible. Opposition can be exercised to control the ongoing power and does not always imply subversion